Pengaruh Bunting dan Laktasi Terhadap Hematologi dan Mineral Kambing Peranakan Ettawa di Kulonprogo, Yogyakarta, Indonesia - Sarmin Sarmin; Amelia Hana; Pudji Astuti; Claude Mona Airin (Jurnal Sain Veteriner, 2020)
The effects of pregnancy and lactation on hematochemical and mineral parameters were evaluated in Ettawa cross-bred goats in Disctrict Kulonprogo, Yogyakarta, Indonesia. Blood plasma samples were collected from 14 th pregnant goats (2 month n=4; 3 month n=6; 4 month n=4) and 16 lactation goats (1 month, n= 4; 2 month, n=5; 3 month, n=3 and 4 month, n=4). Blood serum samples were collected from 18 pregnanct goats (1 month, n=3; 2 month, n=2; 3 month, n=6; 4 month, n=4) and 16 lactation goats (1 month, n=4; 2 month, n=5; 3 month, n=3; 4 month, n=4).  The does averaged 2.5-4 years old and their mean body weights were 30-40 kg. The current result showed that pregnant does recorded higher (p<0.05) values of RBCs and hematocrites compared to lactating does. The higher RBCs during the first and third month of pregnantion and the higher hematocrites values during the first of pregnantion. There were not significant differences in MCV, MCH, MCHC, neutrophyls,  limphocytes, monocytes, WBCs, eosinophyls, and minerals Mg2+, in organic  , Na+, K+ and Cl-during pregnantion and lactation.  The results indicated that pregnantion and lactation has significant effect on RBCs and hematocrites of Ettawa crossbred goats in district Disctrict Kulonprogo, Yogyakarta, Indonesia